2021
DOI: 10.3389/fmed.2021.709642
|View full text |Cite
|
Sign up to set email alerts
|

Incidence and Mortality of Acute Respiratory Distress Syndrome in Patients With Burns: A Systematic Review and Meta-Analysis

Abstract: Objective: We conducted a systematic review and meta-analysis to comprehensively estimate the incidence and mortality of acute respiratory distress syndrome (ARDS) in overall and subgroups of patients with burns.Data sources: Pubmed, Embase, the Cochrane Library, CINAHL databases, and China National Knowledge Infrastructure database were searched until September 1, 2021.Study selection: Articles that report study data on incidence or mortality of ARDS in patients with burns were selected.Data extraction: Two r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 38 publications
0
8
0
Order By: Relevance
“…For total intensive care unit patients with ARDS, the mortality of moderate ARDS and severe ARDS was 40.3% and 46.1%, respectively [ 42 ]. A recent systematic review found that the overall mortality of burn patients with ARDS was 27% [ 5 ]. As for the different subgroups of ARDS, the reported mortality of moderate ARDS was 36.1% [ 43 ] and 20.9% [ 44 ], and the mortality of severe ARDS was 43.8% [ 43 ] and 50% [ 44 ] in different studies.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For total intensive care unit patients with ARDS, the mortality of moderate ARDS and severe ARDS was 40.3% and 46.1%, respectively [ 42 ]. A recent systematic review found that the overall mortality of burn patients with ARDS was 27% [ 5 ]. As for the different subgroups of ARDS, the reported mortality of moderate ARDS was 36.1% [ 43 ] and 20.9% [ 44 ], and the mortality of severe ARDS was 43.8% [ 43 ] and 50% [ 44 ] in different studies.…”
Section: Discussionmentioning
confidence: 99%
“…A survey of 6212 burn deaths showed that burn shock, cardiogenic shock or lung injury, and sepsis or multiple organ failure were the main causes of death within the first week, weeks 1 to 2, and after 2 weeks, respectively [ 2 ]. The incidence of burn-induced acute respiratory distress syndrome (ARDS) is reported to be 2–53% and mortality is 14–68% [ 5 ]. Cardiac stress, characterized with tachycardia, systolic dysfunction, increased cardiac output and energy expenditure, is the hallmark of severe burns and persists for up to 3 years after burns [ 6 ].…”
Section: Introductionmentioning
confidence: 99%
“…They also found that explosion injury did not independently increase the risk of ARDS, despite pulmonary contusion being a known risk factor for ARDS (20). The other nonmodifiable risk factors including pulmonary injury (14), blunt trauma (16), and II (14) could be causative as indicated by civilian literature (11, 46), whereas higher MISS (20) and higher ISS (5) may be more indicative of severe injury, though more studies are needed to investigate causation.…”
Section: Discussionmentioning
confidence: 99%
“…Trauma is a well-defined etiology of ARDS, and there have been a number of studies summarizing its literature and characterizing it in the civilian trauma population (5)(6)(7)(8)(9)(10)(11). However, data specific to combat trauma-related ARDS are lacking.…”
mentioning
confidence: 99%
“…Severe trauma and burn injury cause a systemic inflammatory response syndrome (SIRS) that can result in acute lung injury (ALI) and cause prolonged intensive care unit stays, complications, and death 1 . Acute lung injury and acute respiratory distress syndrome (ARDS) remain significant clinical problems for patients who experience severe injury, with mortality rates approaching 31% 2 . Dysregulation of the immune system as part of SIRS is a principal driver of lung inflammation 3 .…”
mentioning
confidence: 99%